“Everyone says ‘safe sex’ but no one ever says ‘safe drugs’, you know?”: Perspectives on the intersection of drug checking services, drug policy and the overdose crisis - Jeff Ondocsin; Lissa Moran; Daniel Ciccarone; Simon Outram; Dan Werb; Nicole Holm; Emily A. Arnold (PLoS ONE, 2025)
Background Overdose deaths have continued to rise in the US despite heightened public attention and resources. Drug checking shows promise for integration into existing services for people who use drugs (PWUD) across North America. Amidst the backdrop of rising overdose deaths and emerging funds for harm reduction initiatives, this manuscript explores the landscape of drug checking services in North America and perspectives on improved integration with a diverse set of PWUD based in San Francisco and North American drug checking experts. Methods Two separate samples of drug checking stakeholders, ‘providers’ and ‘clients’ were recruited. Providers participated in in-depth semi-structured qualitative interviews over Zoom on their experiences advocating for and operating drug checking services in the US and Canada. Clients were people who used drugs and lived in or commuted to the San Francisco Bay Area and participated in semi-structured interviews in November 2022. Interviews were transcribed fully and analyzed using thematic analysis methods. Results Providers and clients identified ongoing instability in the North American drug supply that is exacerbating overdose risk while also identifying groups that would benefit from greater access to drug checking services. Both groups believed the paradoxical impacts of the fentanyl crisis at the core of drug checking services created barriers to the implementation and expansion of these services, hurting PWUD and their providers. Additionally, clients and providers reflected on the social and policy challenges to expansion and improvement of drug checking in their communities. Conclusion Drug checking remains underleveraged, particularly with respect to the most vulnerable PWUD. Clients and providers contended that these services must become more responsive to an ever changing and dangerous drug supply in North America.